The relationship between low carbohydrate availability, mucosal immunity, and respiratory illness in endurance athletes: mechanisms and practical implications: A Narrative Review - Czmok, Jakub; Półtorak, Katarzyna; Tarczyński, Dominik; Zięba, Natalia; Czech, Mateusz; Cisłak, Miłosz; Chojęta, Michał; Ciesielska, Dominika; Mazur, Anna; Brzusek, Mikołaj; Kociuba, Katarzyna (Quality in Sport, 2026)
Background: Low carbohydrate availability (LCA) is frequent in endurance sports because of high training load, train-low strategies, and body composition goals. Mucosal immunity, especially salivary secretory IgA, is a key barrier against upper respiratory illness. Aim: To summarize links between LCA, mucosal immunity, and respiratory illness in endurance athletes and outline practical implications. Materials and methods: Non-systematic search in PubMed and Google Scholar (2015-2026) using terms related to endurance athletes, LCA, LEA, mucosal immunity, sIgA, respiratory illness, cortisol, and glycogen depletion. Results: Evidence suggests that reduced carbohydrate availability, particularly when glycogen stores are low, may increase stress-hormone responses, limit fuel for immune cells, and impair salivary defense. Intervention and observational studies indicate possible carbohydrate-specific effects on immune markers, but direct causal evidence for confirmed infection outcomes remains limited. Conclusions: Periodized carbohydrate intake, timely refueling around key sessions, and monitoring of sleep, stress, and symptoms may help preserve mucosal immunity and reduce respiratory illness risk.